Postoperative nursing of a patient with perianal necrotizing fasciitis complicated with diabetic ketoacidosis (1例肛周坏死性筋膜炎合并糖尿病酮症酸中毒患者的术后护理体会) - LI Panpan (李盼盼); YUAN Aimin (袁爱民) (中西医结合护理)
This article summarized the postoperative nursing measures for a patient with perianal necrotizing fasciitis (PNF) complicated with diabetic ketoacidosis (DKA). The given vacuum sealing drainage (VAS) was adopted for wound repair, and multi-modal nursing measures including Traditional Chinese Medicine debridement, nutrition support emotional care and health education were carried out to reduce the pain degree and the incidence of complications, and improve the wound healing. (本文总结1例肛周坏死性筋膜炎(PNF)合并糖尿病酮症酸中毒(DKA)患者的术后护理经验。通过负压引流(VSD)辅助治疗, 以及中医化腐清创治疗、营养支持、情志护理以及健康宣教等多元化的护理配合, 有助于减轻患者机体疼痛感, 降低并发症发生率, 加快创面愈合。)